Potássio : fontes alternativas, tratamentos térmicos e disponibilidade para plantas de milho (Zea Mays L.) - Martins, Caroline Cândida (2014)
Our country is one of the most important agricultural producers in the world and it is highly dependent on fertilizers importation, mainly potassium. Aiming to reduce this dependency, material originated from rocks is being tested for this element supply.